A Population‐Based Intervention to Improve Care Cascades of Patients With Hepatitis C Virus Infection. Issue 3 (7th November 2020) - Scott, John; Fagalde, Meaghan; Baer, Atar; Glick, Sara; Barash, Elizabeth; Armstrong, Hilary; Kowdley, Kris V.; Golden, Matthew R.; Millman, Alexander J.; Nelson, Noele P.; Canary, Lauren; Messerschmidt, Matthew; et al.
Abstract : Hepatitis C virus (HCV) infection is common in the United States and leads to significant morbidity, mortality, and economic costs. Simplified screening recommendations and highly effective direct‐acting antivirals for HCV present an opportunity to eliminate HCV. The objective of this study was to increase testing, linkage to care, treatment, and cure of HCV. This was an observational, prospective, population‐based intervention program carried out between September 2014 and September 2018 and performed in three community health centers, three large multiclinic health care systems, and an HCV patient education and advocacy group in King County, WA. There were 232, 214 patients included based on criteria of documented HCV‐related diagnosis code, positive HCV laboratory test or prescription of HCV medication, and seen at least once at a participating clinical site in the prior year. Electronic health record (EHR) prompts and reports were created. Case management linked patients to care. Primary care providers received training through classroom didactics, an online curriculum, specialty clinic shadowing, and a telemedicine program. The proportion of baby boomer patients with documentation of HCV testing increased from 18% to 54% during the project period. Of 77, 577 baby boomer patients screened at 87 partner clinics, 2, 401 (3%) were newly identified HCV antibody positive. The number of patients staged for treatment increased by 391%, and those treated increased by 1, 263%. Among the 79% of patients tested after treatment, 95% achieved sustained virologic response. Conclusion : A combination of EHR‐based health care system interventions, active linkage to care, and clinician training contributed to a tripling in the number of patients screened and a more than 10‐fold increase of those treated. The interventions are scalable and foundational to the goal of HCV elimination.